Extraction socket sealing using palatal gingival grafts and resorbable collagen membranes - Sang-Yun Kim (Maxillofacial Plastic and Reconstructive Surgery, 2017)
Abstract Background Socket sealing surgery is performed for the preservation of the form and volume of the soft tissue by covering the resulting socket with autogenous soft tissue graft or membrane barriers. This procedure is usually necessary to improve the esthetic results of the maxillary anterior or premolar areas. Methods This study retrospectively investigated cases involving the open membrane technique or socket sealing surgery with a palatal gingival graft or collagen membrane where implant placement and bone grafting were performed immediately after tooth extraction. From January 2005 to December 2008, socket sealing surgery was performed in 24 patients, and 25 implants were placed. Results All implants were successful in the follow-up period. In the palatal gingival graft group, the mean marginal bone loss was 1.17 mm during the mean follow-up period of 81.0 months. In the collagen membrane group, the mean marginal bone loss was 1.23 mm during the mean follow-up period of 76.9 months. There was no significant difference between the two groups. Conclusions Consequently, socket sealing surgery is effective at minimizing the loss of soft tissue and alveolar bone.